STUDENT WORKSHEET DEVELOPMENT BY USING BRAIN BASED LEARNING APPROACH TO ENHANCE STUDENT’S PERFORMANCE AT KINEMATICS OF RECTILINEAR MOTION OF 10ST GRADE SMA NEGERI 1 MLATI - Abdul Syukur Asep; Astono Juli (Universitas negeri Yogyakarta, 2016)
Purposes of the study are 1) to produce a proper Student Physics Worksheet by using Brain Based Learning approach so it can enhance student physics performance. 2) to find out which performance that are facilitated by the worksheet.The study is development study which adopted 4D development model from Thiagaradjan, Semmel, and Semmel. The procedures include four phases: (1) Defining, which consists of initial analyze, student analyze, task analyze, concept analyze dan formulation of learning purposes, (2) Designing, which consists of conducting criteria, choosing media, choosing type of presentation, dan conducting initial design, (3) Developing, which consists of expert validation and development trial, and (4) Disseminating. Feasibility of learning instrument is judged by expert and reviewed at content, language, and graphic. Data of study are obtained from expert validation, assessment of pretest and post test, and observation of students affective and psychomotor when trial are done at SMAN 1 Mlati Yogyakarta.The result of this study is physics learning instrument as brain based learning student worksheet that enhance student performance. Based on expert judgement, the worksheet has meet feasible criteria with average score 3,5 which is categorized as “very good”. While students responses to the worksheet have obtained score 3,341 which is categorized as “good”. Student preformance also indicated the enhancement of kinematics rectilinear motion mastery with average gain value is about 0,375 which is categorized as “average”. Student affective performance on average by 84% with “very good” criteria. And student psychomotor performance on average by 94% with “very good” criteria.Key words: development, student worksheet, brain based learning approach, student performance.